A comparative study of two aging and fusion methods in the synthesis of zeolitic materials from natural clinker (2015)
A sample of Colombian natural clinker was evaluated as a raw material in a laboratory-scale synthesis of zeolitic materials using two methods of alkaline fusion, followed by two aging methods, and finally hydrothermal treatment during three different periods of time. Fusion was carried out with solid and aqueous NaOH and followed by static or ultrasonic aging. The process ended with a hydrothermal reaction. Natural clinker was converted into several zeolitic materials. The characteristics of the resulting zeolitic materials and the effects of experimental variations are discussed.